Modified Equations for Optimisation of Retrofitting Techniques in Masonry Buildings - Abdul Razak, Abdul Karim; Norazzlina, M.Sa'don; Mahshuri, Yusof (Universiti Malaysia Sarawak (UNIMAS), 2017)
This research produces modified equations for developing a comprehensive procedure in designing bolted timber connections in local hardwoods. The retrofitting technique of wall-diaphragm connections in masonry buildings can be optimised using the proposed modified equations. It can be seen that not only the enhanced connection strength can be achieved, the present research works also promoting an economical design as less steel fabrication is required.